2003
DOI: 10.1007/s00441-003-0744-y
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyte-mediated phagocytosis and melanization in the mosquito Armigeres subalbatus following immune challenge by bacteria

Abstract: Mosquitoes are important vectors of disease. These insects respond to invading organisms with strong cellular and humoral immune responses that share many similarities with vertebrate immune systems. The strength and specificity of these responses are directly correlated to a mosquito's ability to transmit disease. In the current study, we characterized the hemocytes (blood cells) of Armigeres subalbatus by morphology (ultrastructure), lectin binding, enzyme activity, immunocytochemistry, and function. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
177
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(187 citation statements)
references
References 41 publications
6
177
0
1
Order By: Relevance
“…In mosquitoes, several transcripts encoding enzymes involved in melanization are induced by a Plasmodium parasite in the midgut of Anopheles gambiae (11), and the resulting induced melanization could kill the ookinetes directly in susceptible mosquitoes and dispose of dead parasites in refractory mosquitoes (12). Phenoloxidase has also been demonstrated to interfere with microbial infection in several insect species (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In some cases melanization, or rather the activity of the enzyme PO, was found to have no or little impact on the killing/ clearance of parasites (24,25) and the melanization reaction was found not to be required for survival of mosquitoes/flies after certain microbial infections (26,27).…”
mentioning
confidence: 99%
“…In mosquitoes, several transcripts encoding enzymes involved in melanization are induced by a Plasmodium parasite in the midgut of Anopheles gambiae (11), and the resulting induced melanization could kill the ookinetes directly in susceptible mosquitoes and dispose of dead parasites in refractory mosquitoes (12). Phenoloxidase has also been demonstrated to interfere with microbial infection in several insect species (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In some cases melanization, or rather the activity of the enzyme PO, was found to have no or little impact on the killing/ clearance of parasites (24,25) and the melanization reaction was found not to be required for survival of mosquitoes/flies after certain microbial infections (26,27).…”
mentioning
confidence: 99%
“…But because mosquito hemocytes are difficult to collect from mosquitoes and cannot be cultured or even maintained for significant amounts of time in vitro, they have received little research attention. Hemocytes phagocytose and melanize large numbers of bacteria, fungi, and malaria parasites (15,24,25,28,29). Several subpopulations of mosquito hemocytes have been characterized, and immunocytochemical and cytochemical assays have demonstrated that these cells are differentially responsive to invading pathogens (24,27).…”
mentioning
confidence: 99%
“…Several subpopulations of mosquito hemocytes have been characterized, and immunocytochemical and cytochemical assays have demonstrated that these cells are differentially responsive to invading pathogens (24,27). For example, cell types are distinguished by ultrastructural characteristics, phagocytic capacity, or the presence and activity of enzymes involved in the melanin biosynthetic pathway (24,28,29,36). It is hypothesized that hemocytes also participate in pattern recognition and mediate the production of immune peptides from the fat body (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immunity in invertebrates consists of humoral and cellular components (3,4). The humoral component includes antimicrobial peptides (5), lectins (6), and the prophenoloxidase (proPO) activation cascade (7); the cellular component includes phagocytosis by circulating hemocytes (8). In Drosophila, the Toll signalling pathway is responsible for defense against Gram-positive bacteria and fungi, while the immune deficiency (Imd) pathway is activated primarily to defend against Gram-negative bacteria.…”
Section: Innate Immunity Is Activated By Distinct Pathogen-associatedmentioning
confidence: 99%